Isolated lymph node recurrence in epithelial ovarian cancer: Recurrence with better prognosis?. (June 2020) - Delangle, Romain; Rossard, Lauranne; Cirier, Julien; Delvallée, Julie; Bendifallah, Sofiane; Touboul, Cyril; Collinet, Pierre; Coutant, Charles; Akladios, Cherif; Lavoué, Vincent; Bolze, Pierre-Adrien; Huchon, Cyrille; et al.
Abstract: Introduction: The aim of this study was to compare overall survival (OS) between women with isolated lymph node recurrence (ILNR) and those with isolated peritoneal localization of recurrence (ICR), in patients managed for epithelial ovarian cancer. Methods: Data from 1508 patients with ovarian cancer were collected retrospectively from1 January 2000 to 31 December 2016, from the FRANCOGYN database, pooling data from 11 centres specialized in ovary treatment. Median overall survival was determined using the Kaplan-Meier method. Univariate and multivariate analyses were performed to define prognostic factors of overall survival. Patients included had a first recurrence defined as ILNR or ICR during their follow up. Results: 79 patients (5.2 %) presented with ILNR, and 247 (16.4 %) patients had isolated carcinomatosis recurrence. Complete lymphadenectomy was performed more frequently in the ILNR group vs. the ICR group (67.1 % vs. 53.4 %, p = 0.004) and the number of pelvic lymph nodes involved was higher (2.4 vs. 1.1, p = 0.008). The number of involved pelvic LN was an independent predictor of ILNR (OR = 1.231, 95 % CI [1.074–1.412], p = 0.0024). The 3-year and 5-year OS rates in the ILNR group were 85.2 % and 53.7 % respectively, compared to 68.1 % and 46.8 % in patients with ICR. There was no significant difference in terms of OS after initial diagnosis (p = 0.18). 3- year and 5-year OS rates after diagnosis of recurrence were 62.6 % and 15.6 % in the ILNR group, and 44 % and 15.7 % in patients with ICR (p = 0.21). Conclusion: ILNR does not seem to be associated with a better prognosis in terms of OS.